Large wind turbines design and economics - Harrison, Robert; Snel, Herman; Hau, Erich (John Wiley Chichester, 2000)
This work provides coverage of the relationship between the design and cost issues of large wind turbines. Using simple principles of engineering science, the authors develop a model for quantifying the weight and cost of variable machine sizes, enabling quantitative comparisons to be made.
Includes bibliographical reference and index
Keywords: Wind turbines -- Design and construction